1980
DOI: 10.1177/28.3.7354217
|View full text |Cite
|
Sign up to set email alerts
|

Differences between the O-acetylated sialic acids of the epithelial mucins of human colonic tumors and normal controls: a correlative chemical and histochemical study.

Abstract: Chemical analyses, together with histochemical assessments, were carried out on specimens of adenocarcinoma of the colon and histologically normal colonic epithelium (from resection margins from cases of carcinoma of the colon). In the epithelial glycoproteins of the normal tissue, both chemical and histochemical investigations indicated that the great majority of the sialic acids contained a side-chain O-acyl substituent located at position C5, whereas the side-chain substitution of the sialic acids of tumor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1980
1980
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…The noted reduction of sialomucin expression during the hypersecretory state by LM and TEM histochemistry was further supported by the lectin cytochemistry. This particular pattern was interesting when compared to epithelial glycoprotein secretion in other areas of the tubular gastrointestinal tract in response to disease processes (Reid et al, 1980(Reid et al, , 1985b. Many intestinal and colonic diseases present a reduction of sulphomucin and a significant increase in sialomucin synthesis and secretion.…”
Section: Discussionmentioning
confidence: 93%
“…The noted reduction of sialomucin expression during the hypersecretory state by LM and TEM histochemistry was further supported by the lectin cytochemistry. This particular pattern was interesting when compared to epithelial glycoprotein secretion in other areas of the tubular gastrointestinal tract in response to disease processes (Reid et al, 1980(Reid et al, , 1985b. Many intestinal and colonic diseases present a reduction of sulphomucin and a significant increase in sialomucin synthesis and secretion.…”
Section: Discussionmentioning
confidence: 93%
“…(iii) Chemical correlation. Chemical studies (Reid et al, , 1978b(Reid et al, , 1979) of epithelial glycoproteins either isolated from formalin fixed colon, or from fresh colon Reid et al, 1975aReid et al, , by 1977 and post fixed, showed that the sialic acids were much more neuraminidase labile after KOH than would have been expected from the histochemical results on the same specimens; although in only a few cases was all the sialic acid removed. These data imply that there is a class of sialic acids which are not neuraminidase or KOH/ neuraminidase labile.…”
Section: (B) Identification Of Sialic Acidmentioning
confidence: 99%
“…This indicates that terminal carbohydrate structures of cellular glycoconjugates in goblet cell mucin are modified in adenomas showing mild or moderate dysplasia. Whether this is due to a different kind of sialic acid being more resistant (17,31,32) to Vibrio cholerae neuraminidase treatment, as suggested by the study of Cooper and Reuter (7), or the presence of other sugar moieties (38,39) in the non-reducing terminus of oligosaccharide chains remains unknown. In some adenomas showing mild or moderate dysplasia an apical linear staining was seen with PNA, VVA and GSA-I1 in focal areas of non-mucinous columnar cells.…”
Section: Discussionmentioning
confidence: 99%